Aplikasi Small Area Estimation Pada Penghitungan Nilai Estimasi Indikator Imunisasi Dasar Lengkap Di Pulau Jawa Dan Bali Tahun 2020 - Zenda Oka Briantiko; Rida Agustina (Seminar Nasional Official Statistics, 2022)
Complete basic immunization is the target of the 2020-2024 RPJMN and is one of the single deprivation indicators of multidimensional poverty, Sustainable Development Goals (SDGs) 1.2.2*. However, only about 57.17 percent of children aged 12-23 months received complete basic immunization in 2020. The availability of health facilities in Java and Bali is more than in other areas, but only Bali Province has met a minimum of 80 percent of the target for the complete basic immunization program. This study was conducted to calculate the estimated value of the complete basic immunization indicator to the district/city level which can be used as a reference in determining priority areas for the complete basic immunization program. The method used is Small Area Estimation of 128 regencies/cities in Java and Bali using Susenas 2020 data for direct estimates and Podes 2018 as explanatory variables. SAE modeling is carried out in two ways, namely by combining all districts/cities in Model-1 and separating districts and cities in Model-2. The calculation results show that there are differences in the explanatory variables used in Model-1 and Model-2. However, Model-1 modeling produces an RSE value 25% more than Model-2 so it can be said that the modeling is more effective.